Profile of dermatophyte infections among rural population: a facility based prospective observational study - Poyyamozhi, J. S.; Lakshmanan, Anandhi (International Journal Of Community Medicine And Public Health, 2018)
Background: Dermatophyte infections are a common but neglected public health problem in rural India. Considering the heterogeneity of presentation and changing trends periodic studies documenting the demographic and clinical profile of these infections may be vital in guiding clinical practice. The objectives of the study were to analyse the demographic, clinical and etiological profile of dermatophyte infections among rural population, presenting to a rural health center. Methods: The current study was a cross sectional study, conducted in the rural health center, Department of Community Medicine and Department of Microbiology, Dhanalaskmi Srinivasan medial College and Hospital, permbalur between January 2017 to June 2017. All patients who are clinically diagnosed to have dermatophytosis in the study setting were included in the study. The relevant skin, nail or hair scrapings were subjected to KOH preparation and culture. Results: A total of 250 subjects were included in the final analysis. The majority (47.20%) of the subjects were between 21 to 30 years. Males constituted 65.60% of the study population. The proportion of participants who worked in agricultural labour/farmer, housewife, industrial skilled worker, housemaid, and businessman was 22.40%, 17.20%, 15.20%, 6.40% and 4.80% respectively The majority (38.80%) of the participants were in lower class and lower middle class (31.20%). The most common clinical diagnosis was tinea corporis seen in 30.8% of the population, followed by tinea cruris in 19.6% and tinea ungium in 7.6% of the population. The most common organism isolated in culture was Trichophyton rubrum (25.2%), followed by Trichophyton mentagrophyte (17.2%), and Trichophyton tonsurans (1.20%). Conclusions: Clinicians need to be aware of the demographic profile, common clinical presentations and changing the etiological profile of dermatophyte infections, especially in rural population.